Plant development. Integration of growth and patterning during vascular tissue formation in Arabidopsis - De Rybel, Bert; Adibi, Milad; Breda, Alice S; Wendrich, Jos R; Smit, Margot E; Novák, Ondřej; Yamaguchi, Nobutoshi; Yoshida, Saiko; Van Isterdael, Gert; Palovaara, Joakim; Nijsse, Bart; Boekschoten, Mark V; et al. (Science (New York, N.Y.), 2014)
Coordination of cell division and pattern formation is central to tissue and organ development, particularly in plants where walls prevent cell migration. Auxin and cytokinin are both critical for division and patterning, but it is unknown how these hormones converge upon tissue development. We identify a genetic network that reinforces an early embryonic bias in auxin distribution to create a local, nonresponding cytokinin source within the root vascular tissue. Experimental and theoretical evidence shows that these cells act as a tissue organizer by positioning the domain of oriented cell divisions. We further demonstrate that the auxin-cytokinin interaction acts as a spatial incoherent feed-forward loop, which is essential to generate distinct hormonal response zones, thus establishing a stable pattern within a growing vascular tissue.
Keywords: Basic Helix-Loop-Helix Transcription Factors; buněčné dělení; Nuclear Proteins; trans-aktivátory; cévní svazky rostlin; Cytokines; Arabidopsis Proteins; jaderné proteiny; Gene Expression Regulation, Developmental; Trans-Activators; genové regulační sítě; transkripční faktory bHLH; cytokiny; Indoleacetic Acids; Gene Regulatory Networks; proteiny huseníčku; Body Patterning; kyseliny indoloctové; regulace genové exprese u rostlin; Gene Expression Regulation, Plant; Aminohydrolases; aminohydrolasy; Arabidopsis; Cell Division; vývojová regulace genové exprese; Plant Vascular Bundle; rozvržení tělního plánu